Dificultades y Desafíos de la Educación Rural de Colombia: explorando las Brechas para un Futuro Educativo (2023)
Rural education faces a number of challenges and difficulties that can limit access and quality of education for students living in rural areas. The needs of schools in cities are different from those of schools in rural areas due to differences in families and communities. Young people in rural areas often have early adult responsibilities due to the way their environment works. Schools in rural areas must combine local traditions with preparation for a more globalized and technological world. However, in Colombia, rural dwellers face disadvantages compared to those in the cities. Improving in-service teacher training in rural areas could raise the quality of education there and cause teachers to stay in these areas, which would be beneficial in reducing social differences in the country. Improving teacher training in rural areas is a major challenge and can make a difference in the education of students in these areas. These gaps may be due to factors such as geographic location, socioeconomic status, lack of educational resources, and quality of education. It is important to address these educational gaps and work to ensure that all students have access to quality education and equal opportunities to learn and grow. Lack of educational incentive programs for students and teachers in rural areas can weaken motivation to improve education. Lack of access to technology. The digital divide affects rural areas, making it difficult to access online educational resources and digital learning opportunities. Addressing these educational gaps requires a comprehensive approach that includes investments in infrastructure, teacher training, family support programs, and policies that address inequalities and exclusions in rural education.